Age-Related Modifications of Diffusion Tensor Imaging Parameters and White Matter Hyperintensities as Inter-Dependent Processes - Pelletier, Amandine; Periot, Olivier; Dilharreguy, Bixente; Hiba, Bassem; Bordessoules, Martine; Chanraud, Sandra; Pérès, Karine; Amieva, Hélène; Dartigues, Jean-François; Allard, Michèle; Catheline, Gwénaëlle (Frontiers in Aging Neuroscience, 2016)
Microstructural changes of White Matter (WM) associated with aging have been widely described through Diffusion Tensor Imaging (DTI) parameters. In parallel, White Matter Hyperintensities (WMH) as observed on a T2-MRI are extremely common in older individuals. However, few studies have investigated both phenomena conjointly. The present study investigates aging effects on DTI parameters in absence and in presence of WMH. Diffusion maps were constructed based on 21 directions DTI scans of young adults (n=19, mean age=33 SD=7.4) and two age-matched groups of older adults, one presenting low-level-WMH (n=20, mean age=78, SD= 3.2) and one presenting high-level-WMH (n=20, mean age=79, SD= 5.4). Older subjects with low-level-WMH presented modifications of DTI parameters in comparison to younger subjects, fitting with the DTI pattern classically described in aging, i.e. Fractional Anisotropy (FA) decrease/Radial Diffusivity (RD) increase. Furthermore, older subjects with high-level-WMH showed higher DTI modifications in Normal Appearing White Matter (NAWM) in comparison to those with low-level-WMH. Finally, in older subjects with high-level-WMH, FA or RD values of NAWM were associated with to WMH burden. Therefore, our findings suggest that DTI modifications and the presence of WMH would be two inter-dependent processes but occurring within different temporal windows. DTI changes would reflect the early phase of white matter changes and WMH would appear as a consequence of those changes.